Biomaterials‐based nanoparticles conjugated to regulatory T cells provide a modular system for localized delivery of pharmacotherapeutic agents. Issue 2 (9th September 2022) - Marshall, Gregory P.; Cserny, Judit; Wang, Chun‐Wei; Looney, Benjamin; Posgai, Amanda L.; Bacher, Rhonda; Keselowsky, Benjamin; Brusko, Todd M.
Abstract: Type 1 diabetes (T1D) presents with two therapeutic challenges: the need to correct underlying autoimmunity and restore β‐cell mass. We harnessed the unique capacity of regulatory T cells (Tregs) and the T cell receptor (TCR) to direct tolerance induction along with tissue‐localized delivery of therapeutic agents to restore endogenous β‐cell function. Specifically, we designed a combinatorial therapy involving biomaterials‐based poly(lactic‐co‐glycolic acid) nanoparticles co‐loaded with the Treg growth factor, IL‐2, and the β‐cell regenerative agent, harmine (a tyrosine‐regulated kinase 1A [DYRK1A] inhibitor), conjugated to the surface of Tregs. We observed continuous elution of IL‐2 and harmine from nanoparticles for at least 7 days in vitro. When conjugated to primary human Tregs, IL‐2 nanoparticles provided sufficient IL‐2 receptor signaling to support STAT5 phosphorylation for sustained phenotypic stability and viability in culture. Inclusion of poly‐L‐lysine (PLL) during nanoparticle‐cell coupling dramatically increased conjugation efficiency, providing sufficient IL‐2 to support in vitro proliferation of IL‐2‐dependent CTLL‐2 cells and primary murine Tregs. In 12‐week‐old female non‐obese diabetic mice, adoptive transfer of IL‐2/harmine nanoparticle‐conjugated NOD.BDC2.5 Tregs, which express an islet antigen‐specific TCR, significantly prevented diabetes demonstrating preserved in vivo viability. These data provide the preclinical basis to develop a biomaterials‐optimized cellular therapy to restore immune tolerance and promote β‐cell proliferation in T1D through receptor‐targeted drug delivery within pancreatic islets.